The solution to the inequality |d + 9| > 3 is d < -12 and d > -6.
Explanation:The question is asking how to solve the absolute value inequality |d + 9| > 3. For this problem, you need to consider two scenarios because an absolute value represents a distance, which can be either positive or negative. For the first scenario, consider the inequality as (d + 9) > 3 which, when simplified, gives us d > -6. For the second scenario, consider the inequality as -(d + 9) > 3, which simplifies to d < -12. That means any value of 'd' that's greater than -6 or less than -12 will satisfy the inequality.
Learn more about Absolute Value Inequality here:https://brainly.com/question/32844662
#SPJ2
Forty-eight pounds of sand are used to fill 12 bags. Miranda uses the five-step problem-solving plan. After completing the Solve step, how many pounds of sand should she find each bag will hold? Enter you answer in the box.
48 lbs / 12 bags
About 4 pounds of sand per bag
Each bag would hold 4 pounds of sand because 48 / 12 = 4
estimate the product by rounding 5 times 5,503
27,515 is the actual answer.
Estimated, it is about 27,500
Hope I helped!
*WILL GET BRAINLIEST ANSWER* !
-4 = x/9 - 8
-x/9 = 4 - 8
-x/9 = -4
x = 4 * 9
x = 36
Which expression is equivalent to (21/2 x 2 3/4)^2
[tex]\((21/2 \times 2 \ 3/4)^2\) is equivalent to \(\frac{13320.25}{16}\)[/tex]
Sure, let's simplify the expression [tex]\((21/2 \times 2 \ 3/4)^2\)[/tex] step by step:
1. [tex]\(21/2\)[/tex] can be simplified to [tex]\(10.5\)[/tex].
2. [tex]\(2 \ 3/4\)[/tex]can be written as an improper fraction: [tex]\(2 \ 3/4 = 8/4 + 3/4 = 11/4\)[/tex].
Now, the expression becomes [tex]\((10.5 \times 11/4)^2\)[/tex].
3. Multiply [tex]\(10.5\) by \(11/4\): \(10.5 \times 11/4 = 115.5/4\)[/tex].
Now, the expression is [tex]\((115.5/4)^2\)[/tex].
4. Square the fraction: [tex]\((115.5/4)^2 = (115.5^2)/(4^2)\)[/tex].
5. Calculate the numerator and denominator separately: [tex]\(115.5^2\)[/tex] in the numerator and [tex]\(4^2\)[/tex] in the denominator.
[tex]\[ \text{Numerator: } 115.5^2 = 13320.25 \][/tex]
[tex]\[ \text{Denominator: } 4^2 = 16 \][/tex]
6. The final result is [tex]\(\frac{13320.25}{16}\)[/tex].
Now, you can simplify this fraction by dividing the numerator by the denominator:
[tex]\[ \frac{13320.25}{16} \div 1 = \frac{13320.25}{16} \][/tex]
find X,Y & all 4 angles
Answer:
x=900/47, y=720/47
4x=5y == 3600/47 (top and bottom angle values)
3x+3y == 4860/47 (left and right angle values)
If you want the values in mixed number form, reply back.
Step-by-step explanation:
You can set this up in many different ways.
First, the inverse angles are always equal, so 4x=5y
Additionally, 2 sets of angles are supplementary, meaning they add up to 180 degrees; they are 4x+3x+3y=180 and 5y+3x+3y=180; both are equal
You could simplify the above two equations to get 7x+3y=180 and 3x+8y=180, meaning that 7x+3y=3x+8y, and 4x=5y
This simplifies to y=4x/5
Additionally, you could add the equations, meaning that 10x+11y=360, and y=4x/5
This gives you the answer:
x=900/47 and y=720/47.
You could check this by plugging the values into the equation, and if you do the math (which, I know, is kind of painful), you get the supposed values, so hooray!
Answer:
The angles measuring 4x and 5y measure: 3600/47
The other two angles measure: 4860/47
Step-by-step explanation:
The angles measuring 4x and 5y are vertical angles. Vertical angles are congruent, so we have one equation: 4x = 5y.
The angles measuring 5y and 3x + 3y form a linear pair. Angles in a linear pair are supplementary, so their measures add up to 180 degrees. That gives us a second equation: 3x + 3y + 5y = 180, or simply 3x + 8y = 180.
We have a system of two equations in two unknowns, so we can solve for x and y.
4x = 5y
3x + 8y = 180
We will use the substitution method.
Solve the first equation for x: x = 5y/4
Substitute 5y/4 for x in the second equation.
3(5y/4) + 8y = 180
15y/4 + 8y = 180
15y + 32y = 720
47y = 720
y = 720/47
Substitute y with 720/47 in the first original equation and solve for x.
4x = 5y
4x = 5(720/47)
4x = 3600/47
x = 900/47
The angles measuring 4x and 5y measure: 4x = 4(900/47) = 3600/47
The other two angles measure: 3x + 3y = 3(900/47) + 3(720/47) = 2700/47 + 2160/47 =4860/47
What is the prime factorization of 150?
the prime factors for 150 are:
2 x 3 x 5 x 5
In exponential form:
2^1 x 3^1 x 5^2
Hope this helps
Answer:
Step-by-step explanation:the prime factors for 150 are:
2 x 3 x 5 x 5
Pan Tomaszewski zarabiał 2000 zł, dostał podwyzke i obecnie zarabia 2500 zł. O ile % podwyższono mu pensję?
we are given
Mr. Tomaszewski earned 2,000 zlotys
so, past salary =2000
he got a raise and currently earns 2,500 zlotys
so, present salary =2500
now, we have to find raised amount
we can use formula
raised amount = (present salary) - (past salary)
now, we can plug values
and we get
raised amount = 2500 - 2000
so, we get
raised amount = 500 zlotys........Answer
In 2000 South Dakota had a population of 754,844. The number of people in South Dakota increased by 7.9% in 2010. What is South Dakota's approximate population in 2010?
814,180. Hope I helped. If i didn't I am sos sorry. I would take 7.9 or .079 to 754,844 to get your number.
The approximate population of South Dakota in 2010 after a 7.9% increase from the 2000 population is 814,477 people.
To find the population of South Dakota in 2010, we need to calculate the increased population based on the given percentage increase. We are provided with a population of 754,844 in 2000 and an increase of 7.9% for 2010.
Here is the step-by-step calculation:
Multiply the population of 2000 by the increase percentage (converted to a decimal):
754,844 x 0.079 = 59,632.68.
Add this increase to the 2000 population to get the 2010 population:
754,844 + 59,632.68 = 814,476.68.
Therefore, the approximate population of South Dakota in 2010 is 814,477 people (rounded to the nearest whole number).
HELP!!!! An electrician cuts a 26 ft piece of wire into two pieces. One piece is two feet longer than the other. How long are the pieces?
Let 1 piece = X
The 2nd piece would be X + 2 feet
Add:
x +x+2 = 26 feet
2x +2 = 26 feet
Subtract 2 from each side:
2x = 24
Divide both sides by 2:
x = 24 / 2
X = 12
One piece is 12 feet the other piece is 14 feet.
How do you turn a percent into a fraction
Step 1: You want to remove the percent sign and then put the number over 100.
Step 2: If the percent is not a whole number then you want to multiply the top and bottom number by 10 but only for every number that comes after the decimal point.
Step 3: Always simplify if possible.
Examples:
43% = [tex]\frac{43}{100}[/tex]
78% = [tex]\frac{78}{100}[/tex] = [tex]\frac{39}{50}[/tex]
0.4% = [tex]\frac{0.4}{100}[/tex] = [tex]\frac{4}{1000}[/tex] = [tex]\frac{1}{250}[/tex]
A gardener transplanted a plant from an indoor pot to an outdoor garden. After 30 days, the plant's height was 18 centimeters. After 90 days, it was 29 centimeters. Write an equation to represent the plants growth where the x is the days and the y is the height of the plant.
Let x is the days and the y is the height of the plant.
Let the change between x and y is linear.
So, the relation between x and y will take the form ⇒ y = ax + b
where a and b are constants.
At x = 30 ⇒ y = 18 ⇒⇒⇒ ∴ 18 = 30 a + b → (1)
At x = 90 ⇒ y = 29 ⇒⇒⇒ ∴ 29 = 90 a + b → (2)
solve (1) and (2) to find a and b
subtract (1) from (2)
∴ 11 = 60 a ⇒⇒⇒ ∴ a = 11/60
substitute at (1) ⇒⇒⇒ ∴ b = 25/2 = 12.5
So, the equation which represents the plants growth is
∴ y = (11/60) x + 12.5
Answer:
Let x is the days and the y is the height of the plant.
Let the change between x and y is linear.
So, the relation between x and y will take the form ⇒ y = ax + b
where a and b are constants.
At x = 30 ⇒ y = 18 ⇒⇒⇒ ∴ 18 = 30 a + b → (1)
At x = 90 ⇒ y = 29 ⇒⇒⇒ ∴ 29 = 90 a + b → (2)
solve (1) and (2) to find a and b
subtract (1) from (2)
∴ 11 = 60 a ⇒⇒⇒ ∴ a = 11/60
substitute at (1) ⇒⇒⇒ ∴ b = 25/2 = 12.5
So, the equation which represents the plants growth is
∴ y = (11/60) x + 12.5
Step-by-step explanation:
m∠1=45° and m∠3=65°
What is m∠4?
2. In right △ABC with right angle B, m∠A=(3x−8)° and m∠C=(x−2)°.
What is m∠A?
47°
67°
25°
92
The measure of angle ∣4 is 250 degrees. The measure of angle ∣A is 67 degrees.
Explanation:To find the measure of angle ∣4, we can use the fact that angles around a point add up to 360 degrees.
We know that ∣1 is 45 degrees and ∣3 is 65 degrees.
To find ∣4, we can subtract the sum of angles ∣1 and ∣3 from 360 degrees.
Therefore, ∣4 = 360 - (∣1 + ∣3) = 360 - (45 + 65) = 360 - 110 = 250 degrees.
To find the measure of angle ∣A, we can use the fact that the sum of the angles in a triangle is 180 degrees.
We know that ∣B is 90 degrees because it is a right angle.
Therefore, ∣A + ∣B + ∣C = 180 degrees.
Substituting the given values, we get (3x - 8) + 90 + (x - 2) = 180. Simplifying the equation, we get 4x + 80 = 180.
Solving for x, we get x = 25.
Substituting x back into the equation for ∣A, we get ∣A = (3(25) - 8) = 67 degrees.
Find the value of x + y for x = 75.9 and y = 2.65.
Answer:
x + y = 75.9 + 2.65 = 78.55
Step-by-step explanation:
To solve x + y given that x = 75.9 and y = 2.65. We will simply substitute the value of x in the equation with it value which is 75.9 and substitute the value of y in the equation with it value which is 2.65.
Therefore we have x + y to be
x+y
= 75.9 + 2.65
= 78.55
Therefore x + y = 78.55
I need help!
Simplifying radical expressions
1)
[tex] \sqrt[3]{135} [/tex]
2)
[tex] - 5 {}^{3} \sqrt{40} [/tex]
3)
[tex] {2}^{3} \sqrt{5} \times {4}^{3} \sqrt{8} [/tex]
Here is the solution...
1) [tex]\sqrt[3]{135} \\[/tex]
Solution
We can rewrite [tex]\sqrt[3]{135} = \sqrt[3]{27} *\sqrt[3]{5}[/tex]
Here, [tex]\sqrt[3]{27} = 3[/tex]
Now substitute the value, we get
[tex]\sqrt[3]{135} = 3 \sqrt[3]{5}[/tex]
The answer is [tex]3\sqrt[3]{5}[/tex]
2) [tex]-5\sqrt[3]{40}
Solution
[tex]-5\sqrt[3]{40} = -5\sqrt[3]{8} *\sqrt[3]{5}[/tex]
Here [tex]\sqrt[3]{8} = \sqrt[3]{2^{3} } = 2\\[/tex]
Therefore, we get [tex]-5*2\sqrt[3]{5} = -10 \sqrt[3]{5}[/tex]
The answer is-10 \sqrt[3]{5}[/tex]
2) [tex]2\sqrt[3]{5} * 4\sqrt[3]{8}[/tex]
Solution
[tex]\sqrt[3]{8} = 2[/tex]
Now plug in the above in the given expression, we get
[tex]2\sqrt[3]{5} * 4*2 = 16\sqrt[3]{5}[/tex] {2*4*2 = 16]
The answer is [tex]16\sqrt[3]{5}[/tex]
Twelve less than the quotient of a number and 7 is -2
(x/7)-12=-2
Add 12 to both sides.
x/7=10
Multiply both sides by 7.
x=70
Final answer: 70
hope this helps :)
Find Values of X and Y for No. 19
Because you can't solve for X and Y at the same time and 40 = 12x + 4 y.
To find the values of x and y in the equation 40 = 12x + 4y, isolate the x term and solve for x, then substitute the value of x into the equation to solve for y.
Explanation:To find the values of x and y in the equation 40 = 12x + 4y, you need to solve for one variable at a time. First, isolate the x term on one side of the equation by subtracting 4y from both sides:
40 - 4y = 12x
Then, divide both sides by 12 to solve for x:
x = (40 - 4y) / 12
Now you have the equation for x in terms of y. To find the values of y, you can substitute the expression for x into the original equation and solve for y.
Learn more about Solving linear equations here:https://brainly.com/question/29775795
#SPJ2
i have 500 pennies. If I spend 6 pennies a day until i can no longer do so, at the end of one of these days i will have exactly how many pennies left?
A) 6
B)8
C)10
D)12
A) is 164 because 6 times 6 is 36. 500 - 36 is 164
what is the approximate distance between the points (-3 -4) and (-8 1) on a coordinate grid
What does -8 1 mean do you mean -8, 1
What is the answer
A.
B.
C.
D.
E.
option A IS correct option.
step by step what is 4 (x - 1) -3 (x + 2)
Answer:
For this expression, you will have to use the distribution property to get your answer.
First, distribute the 4 to the x and -1
[tex]4(x)=4x[/tex]
[tex]4(-1)=-4[/tex]
[tex]4x-4-3(x+2)[/tex]
Now do the same with the -3, x and 2
[tex]-3(x)=-3x[/tex]
[tex]-3(2)=-6[/tex]
[tex]4x-4-3x-6[/tex]
Now combine like terms to get your final answer
[tex]4x-3x=x[/tex]
[tex]-4-6=-10[/tex]
Thus, your solution is: x - 10
Step one: 4(x-1)-3(x+2)=0 (set equal to zero)
Step two: 4x-4-3x-6=0 (multiply numbers on the outside to inside of "( )")
Step three: x-10=0 (combine like terms)
Step four: 0+10=10, x=10 (inverse operation)
Answer: x=10
I'm confused like in #1 the positive is five but what do I put for the negative
You found $5, so it's positive. You don't put anything in the negative, because you aren't losing anything.
a student found the product of 8 x 10 to the 6 power + 5 x 10 to the 9th power to be 4 x 10 to 15 power what is the error
8*10^6+5*10^9 should be
5,008,000,000
Answer:
The error student make is he multiply the terms instead of addition.
Step-by-step explanation:
Given : A student found the product of 8 × 10 to the 6 power + 5 × 10 to the 9th power to be 4 × 10 to 15 power.
To find : What is the error ?
Solution :
8 × 10 to the 6 power - [tex]8\times 10^6[/tex]
5 × 10 to the 9th power - [tex]5\times 10^9[/tex]
4 × 10 to 15 power - [tex]4\times 10^{15}[/tex]
According to student, [tex]8\times 10^6+5\times 10^9=4\times 10^{15}[/tex]
We solve the expression,
[tex]=8\times 10^6+5\times 10^9[/tex]
[tex]=8\times 10^6+5000\times 10^6[/tex]
[tex]=10^6(8+5000)[/tex]
[tex]=5008\times 10^6[/tex]
The error student make is he multiply the terms instead of addition.
Alicia bought 4 T-shirts for $23.00. Using the unit rate, how much would 6 T-shirts cost?
i think that you would just take 23/4=$5.75
so take 6 times 5.75 and you should get $34.5
To answer this question, we first need to determine the unit cost (cost per t-shirt).
Step 1: Find the unit cost
Alicia bought 4 T-shirts for a total of $23.00. To calculate the cost per T-shirt (the unit rate), we need to divide the total cost by the number of T-shirts.
So, $23.00 (total cost) divided by 4 (number of T-shirts) equals $5.75. Thus, the unit cost of one T-shirt is $5.75.
Step 2: Calculate the cost for 6 T-shirts
Now that we know the unit cost, we can find out how much 6 T-shirts will cost. To do this, we multiply the unit cost by the number of T-shirts.
So, $5.75 (cost per T-shirt) times 6 (number of T-shirts) equals $34.50.
Therefore, it would cost $34.50 for 6 T-shirts, given the unit rate.
What expression is equivalent to 18 1/5 - (-22 2/5) - (-40 1/5)
Decide which of the two given prices is the better deal and why. You can buy shampoo in a 6 ounce bottle for $2.49 or in a 14 ounce bottle for $9.79. What is the cost per ounce for each bottle?
The cost per ounce of the first bottle is $0.415 and the second bottle is $0.699.
The first bottle has the better deal because if you were to have 14 ounces of the first type of shampoo, it would only cost $5.81
Cost per ounce is:
$0.42 per ounce for the 6 ounce bottle $0.70 per ounce for the 14 ounce bottleTo find the cost per ounce for each bottle, use the formula:
= Total cost / number of ounces
6 ounce bottle:
= 2.49 / 6
= $0.42 per ounce
14 ounce bottle:
= 9.79 / 14
= $0.70 per ounce
The 6 ounce bottle is therefore the better deal.
Find out more at https://brainly.com/question/8158263.
Complete the proof showing that DE is parallel to AC
Answer: The statement is [tex]\frac{AD}{DB} +1=\frac{CE}{EB}+1[/tex] and the reason is add 1 both sides.
Explanation:
The given equation is [tex]\frac{AD}{DB} =\frac{CE}{EB}[/tex].
We know that according to the addition property the equation x=y and x+c=y+c are equivalent equations, where c is a constant.
So we can add 1 both sides in the given equation.
[tex]\frac{AD}{DB} +1=\frac{CE}{EB}+1[/tex]
Now we can take LCM and we get,
[tex]\frac{AD+DB}{DB} =\frac{CE+EB}{EB}[/tex]
The above step is the third step of the given proof. By follow the given steps we can prove that DE is parallel to AC.
Therefore, the missing step is addition of 1 on both the sides of the given equation.
To prove that DE is parallel to AC, we need to show that the lines DE and AC have the same slope. By rearranging the given equations to isolate the currents I₁, I₂, and I₃, and then setting these expressions equal to each other, we can determine the relationship between the currents and thereby the slopes of DE and AC.
Explanation:To prove that DE is parallel to AC, we need to show that the lines DE and AC have the same slope. The given equations 1₁ - 12 - 13 = 0, I₁ R₁ + I₂ R₂ = V₁, and I₂ R₂ − I₃ (R₃ + R₄) = V₂ can be rearranged to isolate the currents I₁, I₂, and I₃ in terms of voltage and resistance. By setting these expressions equal to each other, we can determine the relationship between the currents and thereby the slopes of DE and AC.
Learn more about Lines and Slopes here:https://brainly.com/question/14511992
#SPJ3
4 1/5 divided by 2/3 express your answer as a mixed number in Simplest form
4 (1/5 ) = 21/5
21 / 5 divided by 2 / 3 equals
21 / 5 * 3 / 2 equals 63 / 10 equals
6 (3 / 10)
A bag contains 3 green marbles and 8 white marbles. Suppose a marble is randomly selected what are the odds in favor of picking a white marbles
Total number of marbles : 3 + 8 = 11
8 are white.
Probability of picking a white one is 8/11
How many pints are in 3 gallons?
3 gallons = 24 pints
Hope this helps you!
Always remember you are a Work Of Art!
-Nicole :) <3
A coffee bean processor can dry 4,815 pounds of coffee beans in 3 hours. Which unit rate correctly reflects the speed of the processor?
A. 1,926 pounds/hour
B. 2,408 pounds/hour
C. 10.13 pounds/minute
D. 26.75 pounds/minute
Answer:
D. 26.75 pounds/minute
Step-by-step explanation:
For calculate unit rate that reflects the speed of the processor we can use the following equation:
[tex]Speed = \frac{Total Pounds}{RequiredTime}[/tex]
Taking into account that the answers are in pounds per hour and pounds per minute, we re going to calculate the speeds in booth units.
1. Speed in Pounds per hours: Replacing Total Pounds by 4,815 and Required time by 3 hours, we get:
[tex]Speed = \frac{4,815Pounds}{3 Hours}=1,605 Pounds/hour[/tex]
2. Speed in Pounds per minute: Every hour have 60 minutes, the 3 hours have 180 minutes, so replacing Total Pounds by 4,815 and Required time by 180 minutes, we get:
[tex]Speed = \frac{4,815Pounds}{180 Hours}=26.75 Pounds/hour[/tex]
So, chosen the rate that appear in the answers, we can say that the correct answer is D. 26.75 pounds/hours.